Gender Differences in Interpersonal Problems of Alcohol-Dependent Patients and Healthy Controls - Mueller, Sandra E.; Degen, Bigna; Petitjean, Sylvie; Wiesbeck, Gerhard A.; Walter, Marc (My University, 2009)
Alcohol dependence is a heavy burden on patients, their families, and society. Epidemiological studies indicate that alcohol dependence will affect many individuals at some time in their lives, with men affected more frequently than women. Since alcohol-dependent patients often exhibit a lack of social skills and suffer from interpersonal problems, the aim of this study is to elucidate whether men and women experience the same interpersonal problems. Eighty-five alcohol-dependent patients (48 men; 37 women) after detoxification and 62 healthy controls (35 men; 27 women) were recruited. Interpersonal problems were measured with the Inventory of Interpersonal Problems (IIP-64). Additionally, alcohol-dependent patients were interviewed with the Alcohol Use Disorders Identification Test (AUDIT) and were subtyped according to Lesch’s Alcohol Typology (LAT). There were no significant gender differences in the AUDIT and LAT between alcohol-dependent men and women. Interpersonal problems of alcohol-dependent men differed significantly in one out of eight dimensions from controls; alcohol-dependent men perceive themselves as colder than male controls. Alcohol-dependent women differed in four out of eight interpersonal dimensions from female controls. Alcohol-dependent women rated themselves as significantly more vindictive, more introverted, more overly accommodating and more intrusive than female controls. Results suggest that alcohol-dependent men and women suffer from different interpersonal problems and furthermore alcohol-dependent women perceive more interpersonal problems, whereas the severity of alcohol dependence did not differ between the groups. Our findings indicate that alcohol-dependent women may profit more from a gender-specific treatment approach aimed at improving treatment outcome than alcohol-dependent men.
Keywords: Medizin; Gesundheit; Geschlecht; Beziehung; Konflikt; Sucht; 613 Persönliche Gesundheit und Sicherheit; Unterschied